Segmental retinal arteritis in a case of presumed bilateral rifabutin-associated hypopyon uveitis - Shefali Sood; Jeanette Du; Allison Chen; Andy Medina; Brian K. Do (American Journal of Ophthalmology Case Reports)
Purpose: To describe the presentation and clinical course of bilateral hypopyon uveitis and subsequently diagnosed segmental retinal arteritis in an immunocompromised patient treated with intravitreal and systemic antibiotics while on rifabutin therapy for pulmonary tuberculosis (TB). Observations: A 63-year-old female from West Africa with a past medical history of HIV/AIDS, hepatitis B, and pulmonary TB presented with pain and acute vision loss in the left eye for two days. She was compliant with her treatment regimen for HIV and maintenance therapy for TB including rifabutin. Ocular examination revealed hypopyon uveitis in the left eye (OS). She was treated with broad spectrum systemic antimicrobials, topical prednisolone acetate, and intravitreal injections of vancomycin, ceftazidime, voriconazole, and ganciclovir, with resolution of hypopyon OS in 3 days. Aqueous sampling and systemic workup were unrevealing for causative infection. Two weeks later, she returned with a nearly identical presentation in the right eye (OD) with hypopyon uveitis and was again treated with intravitreal antibiotics. Anterior segment inflammation OD quickly improved after initiation of topical prednisolone acetate 1 % to reveal segmental retinal arteritis on fundus examination. As aqueous sampling was negative for infectious causes, she was diagnosed with presumed rifabutin associated-hypopyon uveitis in both eyes (OU) and segmental retinal arteritis OD, which has not been described previously with rifabutin use. Rifabutin was discontinued and there were no recurrences of uveitis over nine months of follow-up. Conclusions and importance/implications: Uveitis is an uncommon dose-related toxicity of rifabutin therapy. Segmental retinal arteritis (SRA) may be a rare finding when there is posterior segment involvement, especially in patients with concurrent TB infection. This report highlights a case of delayed bilateral hypopyon-uveitis and expands the presentation to include SRA. Patients treated with rifabutin should be counseled on signs and symptoms of uveitis. Development of rifabutin-associated uveitis may require medication discontinuation.